If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -3p = -8p + -15 + -7 Reorder the terms: 13 + -3p = -15 + -7 + -8p Combine like terms: -15 + -7 = -22 13 + -3p = -22 + -8p Solving 13 + -3p = -22 + -8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '8p' to each side of the equation. 13 + -3p + 8p = -22 + -8p + 8p Combine like terms: -3p + 8p = 5p 13 + 5p = -22 + -8p + 8p Combine like terms: -8p + 8p = 0 13 + 5p = -22 + 0 13 + 5p = -22 Add '-13' to each side of the equation. 13 + -13 + 5p = -22 + -13 Combine like terms: 13 + -13 = 0 0 + 5p = -22 + -13 5p = -22 + -13 Combine like terms: -22 + -13 = -35 5p = -35 Divide each side by '5'. p = -7 Simplifying p = -7
| 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 | | 0.66x+1=0.50 | | ln(5x+1)=ln(x+11) | | 9x=-11.7 | | 65x-6x=21x+23 | | 6x+6=6(x-5) | | 17h-13h-4h+2h=14 | | 7x-15-10x=15 | | 8x-5=32x-13 | | 11k-9+2k-3= | | 2b+8=2 | | X-8/3=1-x8 | | -1/2•-7=-11 | | -6x-36=-7(1+5x) | | 8b-a-b+a= | | y=1.1 | | (m-7)(m-7)=49 | | Y-3=6(x-6) | | x+(16+x)=184 |